PENGARUH LIKUIDITAS, AKTIVITAS, GOOD CORPORATE GOVERNANCE (GCG) DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - Istianah Istianah; Roni Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis study aims to determine the effect of Liquidity, Activity, Good Corporate Governance (GCG) and Firm Size on Stock Price.This research is a quantitative research using secondary data in the form of data obtained from financial statements. The population used in this study is Food and Beverage companies listed on the Indonesia Stock Exchange 2014-2016. Technique of this research sample use purposive sampling method which amounted to 13 companies. Data analysis using multiple linear regression analysis.Based on the results of this research, Liquidity, Activity, Good Corporate Governance (GCG) and Firm Size has positive and significant impact on Stock Price.Keywords: Liquidity, Activity, Good Corporate Governance (GCG), Firm Size and Stock Price.